The Effects of Ingesting a High-fat Diet on Wistar Rats Chronically Infected with Trypanosoma cruzi - José Leonardo Paredes; Elio Moreno; Gloria Premoli; Maritza Alarcón; Ana Lugo De Yarbuh; Juana Villarreal; Sonia Araujo; Rafael Borges (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2009)
The effects of ingesting a high fat diet on albino rats (R. norvegicus) chronically infected with Trypanosome cruzi "Planalto" were researched using serological and parasitological diagnostic tests, body mass index (BMI) quantification, detection of C-Protein Reactive (CPR), evaluation of the plasmatic lipid levels (total cholesterol, high density lipoproteins HDL and triglycerides) and the presence of lipidic deposits in the aorta artery. During the course of the chagasic infection, patent parasitemias were detected between the ages of 10 and 35 days post-infection (pi) with a maximum average of 36.68 ± 2 tryps/mm³ of blood at 25 days. At 90 days pi, the absence of parasitemias and the presence of IgG anti T. cruzi antibodies were in evidence. The chagasic rats in chronic phase (A) and the healthy controls (C) submitted to a high fat diet showed: 1. Significant variations (p0.05) in the BMI, in comparison with the rat groups receiving a normal diet (B: infected and D: healthy rats); 2. A discrete CRP reaction in the serum of infected rats B; 3. A significant increase was shown in the total cholesterol levels, HDL cholesterol and triglycerides for groups A and C in comparison with control groups B and D (p0.05). The histological study of rat arteries in group A revealed important lipid deposits located in the muscular layer near the intimal and adventitial layer. These results suggest that the increase in plasmatic lipid levels stimulated by the infectious process are the main mechanisms through which T. cruzi could be influencing the initiation or the progression of atheromatous plaque.